Traversing the Divide Honouring Deborah Cass's Contributions to Public and International Law - Rubenstein, Kim (ANU Press, 2021)
While devoting fine attention to the stuff of everyday life, Deborah Cass was also a brilliant scholar. Although the deep sense of loss and sadness at Deborah's death remains, it is wonderful to have her writings as a continuing source of inspiration and consolation. In them, we continue to hear Deborah's firm, clear voice, her appreciation of language, her seriousness, her curiosity, her sensitivity and her wry humour.' -Professor Hilary Charlesworth This collection honours the work of Deborah Cass, 15 February 1960 - 4 June 2013, a brilliant Australian constitutional and international lawyer. Deborah studied at the University of Melbourne and Harvard Law School and taught at Melbourne Law School, The Australian National University and the London School of Economics. A member of The Australian National University's Centre for International and Public Law from 1993 to 2000, Deborah's work offered illuminating new perspectives in a range of fields, from the right to self-determination, critical international legal theory, and feminist legal theory to the international trade law system. The title of this edited collection draws on one of her articles, 'Traversing the Divide: International Law and Australian Constitutional Law' (1998) 20 Adelaide Law Review 73. This book evolves from a symposium held to draw together academics from around the globe to reflect on Deborah's extensive scholarship and contributions to public law and international law, and to examine how her work is of value to current domestic and international law issues. The pieces selected for this volume both remind us of Deborah's outstanding academic career and provide important insights on current public law and international law pressing issues.